Clinical Characteristics of Pediatric Esophagitis in Southern Iran; A Single-Center Experience - Mozhgan Zahmatkeshan; Khadijesadat Najib; Bita Geramizadeh; Ebrahim Fallahzadeh; Mahmood Haghighat; Mohammad Hadi Imanieh (Iranian Journal of Medical Sciences, 2013)
Background: We sought to determine the clinical characteristics of pediatric esophagitis in southern Iran. Methods: This cross-sectional study was conducted over a 4-year period, from 2005 to 2009, in Nemazee Hospital, a tertiary healthcare center in Shiraz, southern Iran. We consecutively included all pediatric patients (<18 years) who underwent endoscopy in our center and had pathology-confirmed diagnosis of esophagitis. Data regarding the patients’ demographic characteristics, comorbidities, and clinical findings were recorded using a questionnaire. All the patients underwent upper gastrointestinal endoscopy and biopsy of the esophagus, and the findings were recorded in the questionnaire. Results: We studied 125 children, comprising 61 (48.8%) girls and 64 (51.2%) boys at a mean age of 6.6±5.5 years. Repeated vomiting was the prominent symptom in our series, with it being reported by 75 (60%) patients, followed by fever in 35 (28%). Erythema (33.6%), esophageal ulcer (11.2%), and whitish patch (8.0%) were the most common endoscopic findings, while reflux esophagitis (32.8%), chronic (6.4%) and acute esophagitis (5.6%), and candida esophagitis (5.6%) were the most common histological diagnoses. Only one (0.8%) patient was diagnosed as having eosinophilic esophagitis, aspergillosis, and graft-versus-host disease. Conclusion: Reflux was the most common cause of esophagitis in the pediatric population of southern Iran. Contrary to previous reports, the prevalence of eosinophilic esophagitis was far less than that estimated, while the prevalence of opportunistic infections was higher secondary to post-liver transplantation immunosuppression.